2017
DOI: 10.3945/ajcn.117.157115
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of intrapericardial and extrapericardial fat tissues during long-term, dietary-induced, moderate weight loss

Abstract: In view of evidence linking pericardial fat accumulation with increased cardiovascular disease risk, strategies to reduce its burden are needed. Data comparing the effects of specific long-term dietary interventions on pericardial fat tissue mobilization are sparse. We sought to evaluate intrapericardial-fat (IPF) and extrapericardial-fat (EPF) changes during weight-loss interventions by different dietary regimens. During 18 mo of a randomized controlled trial, we compared a Mediterranean/low-carbohydrate (MED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Giugliano and Esposito have suggested that Mediterranean diet could also be beneficial in chronic inflammation associated with visceral obesity, type 2 diabetes, and metabolic syndrome [ 14 ]. Recently, the Mediterranean diet was also found superior to a low-fat diet in reducing intrapericardial-fat burden in a randomized controlled trial [ 15 ], hinting their potential in preventing cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Giugliano and Esposito have suggested that Mediterranean diet could also be beneficial in chronic inflammation associated with visceral obesity, type 2 diabetes, and metabolic syndrome [ 14 ]. Recently, the Mediterranean diet was also found superior to a low-fat diet in reducing intrapericardial-fat burden in a randomized controlled trial [ 15 ], hinting their potential in preventing cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…27 Further to that, mobilization of ectopic fat depots was associated with improved cardiometabolic surrogate markers such as decreased expression of atherogenic dyslipidemia. 27,28 Skeletal muscle secretome. Upon contraction, skeletal muscle fibers express and release cytokines and other peptides, which encompass a group of hormone-like substances referred to as myokines.…”
Section: An Integrative View On Atherosclerosismentioning
confidence: 99%
“…80 Moreover, a significant association between pericardial adipose tissue and the SAT ratio with insulin resistance was found, independent of body mass index and VAT, 81 and total intrathoracic adipose volume proved to be associated with cardiac contractile dysfunction in patients with coronary artery disease. 82 Interestingly, dietary-induced reduction of pericardial adipose tissue was independently associated with an improved lipid profile, 83 indicating that intrathoracic adipose depots, like VAT and SAT, are dynamic compartments that can decrease with lifestyle modification. 83…”
Section: Chest: Pericardial and Intrathoracic Adipose Tissuementioning
confidence: 99%
“…82 Interestingly, dietary-induced reduction of pericardial adipose tissue was independently associated with an improved lipid profile, 83 indicating that intrathoracic adipose depots, like VAT and SAT, are dynamic compartments that can decrease with lifestyle modification. 83…”
Section: Chest: Pericardial and Intrathoracic Adipose Tissuementioning
confidence: 99%